Assessment of Trace Elements in Plantago holosteum Scop. (Plantaginaceae) from Abandoned Tungsten Mine Works Using Inductively Coupled Plasma–Mass Spectrometry. (22nd January 2018) - Arslan, Hülya; Erdemir, Ümran Seven; Güleryüz, Gürcan; Kiazolu, Hawa; Güçer, Şeref
ABSTRACT: The influence of tungsten on the uptake and translocation of essential elements (B, Bi, Cd, Co, Cr, Cu, Fe, Mn, Mo, Pb, Zn, and W) of Plantago holosteum around the abandoned tungsten mine works on Uludağ Mountain, Turkey was evaluated. Open-wet and Kjeldahl digestion procedures were applied to the samples before elements were determined by inductively coupled plasma–mass spectrometry. Accuracy was evaluated using standard tea and spinach leaf and soil-certified reference materials. The novel approach of this work identified P. holosteum as a possible candidate bioaccumulator species, which was widespread in the tungsten mining area and provided overall, realistic evaluations for many elements, particularly W. Thus, the specific behavior of the selected species separated this species from the others in this damaged ecosystem. The W concentrations in soils and plants were in the range from 6 to 2591 mg kg −1 dry weight and 0.6 to 85.3 mg kg −1 dry weight, respectively. The concentrations of elements in soil samples from the waste removal pool were higher than those from the unpolluted sites, and all elements except manganese increased in plant samples.